A MORPHOLOGICAL READING OF J.K. ROWLING’S NOVELS USING PROPP’S NARRATIVE THEORY - Hidayatul Nurjanah; Asyida Hayati Shofa (Universitas Respati Yogyakarta (UNRIYO), 2023)
Narratology study has been debate from scholars from myth to postmodern times. However, although postmodern thinkers put aside a set rule of narrative, yet in fact in there are found numerous generous amount of narrative by incorporating the world and the self. This research attemps at applying morphological perspective of Propp’s narrative functions in J.K. Rowling’s novels such as Harry Potter and the Philosopher's Stone, Harry Potter and the Chamber of Secrets, and Fantastic Beasts and Where to Find Them. Using qualitative content analysis approach, this research was conducted by doing documentation, examination, and classification to obtain the relevant data. The result shows that there are identified 19 functions in Harry Potter and the Philosopher's Stone which written using propp’s nomeclature symbols as βγ2δεη1θ1A14CDEG6J1K5ExI1↑, and then 21 functions in Harry Potter and the Chamber of Secrets written in nomeclature symbols β2γδε2ζη3θA1aBCDEF5G3H2I2Rs1MNQ1, and 13 functions in Fantastic Beasts and Where to Find Them written in nomeclature symbols αδ[η1η2η3]A13a3C[E7E8][F1F2F4F5F7]GH1I2[K2K5K6K7K10]Rs5Q3. In addition, J.K. Rowling’s novels which widely accepted as postmodern literary works are still relevant to Propp’s morphologic model of narrative functions approach. In short, Propp’s theory is applicable for the study of narrative not only for folktale but also other literary genres.